2012
DOI: 10.1007/s00167-012-1988-4
|View full text |Cite
|
Sign up to set email alerts
|

Transtibial versus low anteromedial portal drilling for anterior cruciate ligament reconstruction: a radiographic study of femoral tunnel position

Abstract: Drilling the femoral tunnel through the low anteromedial portal resulted in a more oblique femoral tunnel position compared to the TT technique. Clinically, the low anteromedial portal may allow to better restore the anatomic orientation of the ACL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
0
25
0
4
Order By: Relevance
“…Pascual-Garrido et al18) reported that the values were 50°±6° and 54°±6°, respectively, when femoral tunneling was performed via the low anteromedial portal in ACL reconstruction using an anteromedial portal, whereas the values were 58°±9° and 59°±12°, respectively, when a transtibial tunnel was for femoral tunneling. Bedi et al17) reported the values as 45.9°±6.9° and 50.0°±7.5°, respectively, after ACL reconstruction using an anteromedial portal for femoral tunneling that was performed with the knee maintained at 120° flexion.…”
Section: Resultsmentioning
confidence: 99%
“…Pascual-Garrido et al18) reported that the values were 50°±6° and 54°±6°, respectively, when femoral tunneling was performed via the low anteromedial portal in ACL reconstruction using an anteromedial portal, whereas the values were 58°±9° and 59°±12°, respectively, when a transtibial tunnel was for femoral tunneling. Bedi et al17) reported the values as 45.9°±6.9° and 50.0°±7.5°, respectively, after ACL reconstruction using an anteromedial portal for femoral tunneling that was performed with the knee maintained at 120° flexion.…”
Section: Resultsmentioning
confidence: 99%
“…Radiographic analysis was the most commonly used method. 15,20,51,59,77 On both anteroposterior and notch views, femoral tunnels drilled independently were more horizontal and oblique when compared with tunnels drilled through the tibia. 15,20,51 Femoral tunnels drilled independently were Vol.…”
Section: In Vivo Studiesmentioning
confidence: 96%
“…Therefore, there is a trend to change the style of surgery from the traditional TT portal technique to the low AM bundle technique. Different studies show a comparison between the results of both techniques 3 .…”
Section: Am or Posterolateral Portal?mentioning
confidence: 99%
“…Pascual-Garrido et al 3 conducted a study aiming to compare the femoral tunnel position after ACL reconstruction by the TT approach versus the AM approach using radiographs from a single surgeon. The postoperative knee radiographs of 50 patients with an ACL reconstruction were studied in two groups according to the tunnel approach.…”
Section: Radiographic Studiesmentioning
confidence: 99%
See 1 more Smart Citation